Knowledge, Attitudes, and Practices in River Sanitation: Perspectives from Riverside-Dwelling Communities in Zamboanga Sibugay, Philippines - Hassan I. Esmael; Kreslie Mae A. Duldulao; Rosalino O. Delosa; Jopeter B. Dela Paz; Randy Ian F. Gallego (Masters Program in Public Health, 2025)
Background: Rivers are crucial to ecosystems, providing water for drinking, agriculture, and recreation, but urbanization and industrial activities have severely degraded their quality. This study aims to examine the knowledge, attitudes, and practices (KAP) of riverside-dwelling residents regarding river sanitation, with the goal of identifying key factors influencing their understanding and behaviors related to water quality and environmental health.Subjects and Method: Employing a descriptive-correlational research design, the study involved 120 randomly selected samples from households within 200 meters of the riverbanks situated in Barangay Basalem, Buug, Zamboanga Sibugay. Data were collected over the period from June 2022 to April 2023 using validity- and reliability-tested questionnaires and analyzed through Pearson correlation coefficients. The dependent variable in the study was the sociodemographic characteristics of the respondents, while the independent variables were the respondents' knowledge, attitudes, and practices related to water sanitation.Results: Results showed high levels of knowledge but varied attitudes and practices. Respondents understood the risks of contaminated water but held contradictory beliefs about sanitation practices. Statistical analysis demonstrated a significant correlation between age and both attitudes (p= 0.049) and practices (p= 0.049) related to river sanitation, highlighting generational differences in river sanitation behaviors.Conclusion: The findings underscore the need for targeted interventions and improved educational programs to address knowledge gaps and promote effective sanitation practices, ultimately aiming to protect both public health and river ecosystems.